STUDIES ON CERTAIN ASPECTS OF THE MORPHO-HISTOLOGY OF INDIAN SHAD HILSA, TENUALOSA ILISHA (HAMILTON) IN RELATION TO FOOD AND FEEDING HABITS - De, D K; Datta, N C (Indian Journal of Fisheries, 2011)
Morphology and histology of the alimentary canal of hilsa, Tenwlosa ilisha (Hamilton) in relation to feeding habit have been studied. The study reveals that the absence of teeth and masticatory organs in the mouth, presence of very fine, numerous elongated closely set gill rakers, pharyngeal pouch, short narrow cylindrical oesophagus, highly developed muscular gizzard like pyloric stomach and moderately long intestine (RLG varies between 0.86 and 1.87) in hilsa show that the species is predominantly microphagous in feeding habit. The results of stomach content analysis of fry, juvenile and adult also give support to the above contention. It is also evident that young hilsa mainly subsist on zooplankton and adult are microphagous planktivore.